MODEL OF CHEMICAL HAZARD RISK FOR DETERMINING HEALTH HAZARD CONTROL - Rizkiyah Nur Putri; M Trifiananto (Universitas Darussalam Gontor, 2019)
The potential dangers that exist in universities under the auspices of PT Semen Indonesia are a reflection of the dangers that exist in the company. With the concept of college location with this company, the danger is suffered by the academic community. AKSI Gresik is a vocational college using company facilities, especially workshop, has the highest potential hazard is chemical hazard. The purpose of this study is to produce information from smart tools that make it easier for academics to identify potential health problems and provide input / recommendations for hazard control against chemical hazard conditions including the danger of sulfur dioxide, carbon monoxide, nitrous oxide, dust, lead, hydrogen sulfide ammonia and carbon monozide. Hazard control includes substitution / elimination of hazards, input from engineering, administration and PPE. The method used is quantitative by measuring in March - April 2019 in the rector's building, lecture building, machine shop and heavy equipment workshop of AKSI GRESIK. The measurement results will be entered into the manufacture of smart tools by using the Java program (NetBeans IDE 18.1. This research produces applications that can be operated on personal computers that indicate the potential for dust hazards as the highest value of chemical impacts. Disturbances suffered in the AKSI GRESIK in the form of respiratory disorders and digestion generated by dust hazards The output of the design of smart tools is the control of hazards offered by the smart tools program designed in this study include engineering by the presence of sensors capable of removing water, isolating certain work sites to using dust respirator masks with special filters which is replaced every day. Keyword: chemical hazards, hazard control, smart tools